Analysis and Impact Evaluation of Entrepreneurs' Improvisational Behavior Trigger Patterns. (10th January 2022) - Liu, Ying; Wang, Sheng-Yuan; Wu, Xiao-Lan; Liang, Jing
Abstract : How entrepreneurial firms can enhance the level of exploratory and exploitative improvisation in a balanced manner to enhance organizational dynamics has become an important research topic. Current research on the triggers of duality entrepreneurial improvisation has just started, exploring mainly abstract characteristic variables, and has not paid attention to the impact of entrepreneurs' daily behaviors. In order to make up for the shortcomings of current research, the research goal of this paper is to construct a triggering model of entrepreneurs' improvisation based on the research of entrepreneurs' daily behaviors and then to evaluate the influence of the improvisational behavior trigger patterns. Based on the paradoxical and theoretical perspective of duality, a structured observation method is used to explore which behavioral patterns of entrepreneurs tend to trigger dual improvisational behaviors in themselves, their teams, and their organizations. After observing and recording the creators and collecting phenomenal data, six entrepreneurial behavior patterns containing 39 specific operational behaviors have been extracted from the phenomenal data by drawing on the rooted theory approach. In addition, the influence of entrepreneurial patterns is evaluated and ranked using the pairwise hesitant fuzzy set evaluation method. This study reveals the relationship between entrepreneurs' daily behaviors and dyadic entrepreneurial improvisation at the operational level and provides guiding plans for entrepreneurs to improve their own and their organizations' improvisation levels.